P227 DOES NITROPRUSSIDE TEST BEHAVE AD AN INCREMENTAL PROGNOSTIC FACTOR IN SELECTION OF PATIENTS CANDIDATE TO LVAD IMPLANTATION?. (18th May 2022) - Cusenza, V; Pidello, S; Frea, S; De Ferrari, GM
Abstract: Background: Left ventricular assist device in the last two decades has been used to improve survival and quality of life of patients suffering from heart failure, regardless presence of concomitant pulmonary hypertension. Most patients showed improvement in pulmonary pressure. Current clinical practice lacks a reliable method for prediction of reverse remodelling and prognosis. Aim: of this study is to investigate the possible role of nitroprusside test as prognostic factor in candidates to LVAD implantation. Methods: We conducted a monocentric prospective observational study analysing 31 consecutive patients implanted with LVAD between July 2013 and October 2021 that underwent right heart catheterization and nitroprusside test before implantation. Basal and nitroprusside–obtained hemodynamic parameters were subsequently correlated with the primary outcome, defined as the composite of death and episodes of right ventricular failure. Results: Mean age of study population was 58, 6 ± 7, 97 years, 12, 9% were female. Most prevalent INTERMACS class was 3 and mean EF was 18 ± 4, 92 %. Mean follow–up was 31, 3 ± 20, 4 months, during which 11 death and 14 episodes of RVF occurred. At basal hemodynamic assessment, patients with pulmonary vascular resistance above 3 WU had a significant higher rate of events (50% vs 9%, Likelihood ratio 5.7, p = 0.029). No hemodynamic parameter measured after nitroprusside infusion was found to predict survival or episode of RVF. Conclusion: In this exploratory study we have shown that nitroprusside infusion does not add further prognostic information when compared with basal hemodynamic parameters.